MiR-875-5p counteracts epithelial-to-mesenchymal transition and enhances radiation response in prostate cancer through repression of the EGFR-ZEB1 axis. (1st June 2017) - El Bezawy, Rihan; Cominetti, Denis; Fenderico, Nicola; Zuco, Valentina; Beretta, Giovanni Luca; Dugo, Matteo; Arrighetti, Noemi; Stucchi, Claudio; Rancati, Tiziana; Valdagni, Riccardo; Zaffaroni, Nadia; Gandellini, Paolo
Abstract: Radiotherapy is one of the main treatment choices for non-metastatic prostate cancer (PCa), although development of radioresistance limits its effectiveness. Mounting evidence supports the ability of microRNAs to interfere with different radioresistance-associated pathways, suggesting their potential as radiosensitizers. Here, we demonstrate that reconstitution of miR-875-5p, whose expression is down-regulated in PCa clinical samples and directly correlates with that of E-cadherin, was able to enhance radiation response in PCa cell lines and xenografts through EGFR direct targeting. Consistent with the established role of EGFR in sustaining epithelial-to-mesenchymal transition (EMT) and promoting DNA repair following radiation-induced nuclear translocation, we found that miR-875-5p reconstitution in PCa cells counteracted EMT and impaired DNA lesion clearance. Down-regulation of the EMT-inducing transcription factor ZEB1, which also plays a role in homologous recombination-mediated repair of DNA lesions by regulating CHK1 expression, was found to be a major determinant of miR-875-5p -induced radiosensitization, as confirmed by phenocopy experiments showing that siRNA-mediated ZEB1 knock-down was able to reproduce the microRNA radiosensitizing effect. Overall, our data support the clinical interest in developing a novel therapeutic approach based on miR-875-5p reconstitution to increase PCa response to radiotherapy. Highlights: miR-875-5p expression is down-regulated in prostate cancer clinical samples. miR-875-5p reconstitution enhances radiation response in prostate cancer models through EGFR direct targeting. Radiosensitization relies on EMT suppression and DNA repair inhibition as a consequence of ZEB1 down-regulation.